Application of a copper-doped bismuth telluride topological insulator diaphragm modification material in lithium-sulfur battery diaphragm field

CN121341956BActive Publication Date: 2026-09-11SOUTH CHINA NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511423704.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-09-11
Estimated Expiration
2045-09-30

AI Technical Summary

Technical Problem

然而,Bi2Te3对多硫化物的吸附性和催化活性还需要进一步提高

Benefits of technology

[0005] The purpose of this invention is to overcome the shortcomings and deficiencies of the prior art and provide a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material. The introduction of Cu enhances the catalytic activity of Bi2Te3 for polysulfide conversion and improves ionic conductivity, thereby improving the charge and discharge performance of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121341956B_ABST
    Figure CN121341956B_ABST
Patent Text Reader

Abstract

This invention provides a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material and its preparation method, with the chemical formula Bi. 2‑x Cu x Bi2Te3, wherein the Cu doping amount x is less than 10%. In this invention, Cu doping alters the surface topology of Bi2Te3, increasing the surface carrier concentration. Furthermore, when used as a separator material in lithium-sulfur batteries, Cu doping induces crystal defects, exposing more sites. Cu and sulfur species can form Cu-S bonds, thus significantly enhancing the ability of bismuth telluride to capture polysulfides. The introduction of Cu improves the catalytic activity of Bi2Te3 for polysulfide conversion, improves ionic conductivity, and thereby enhances the charge-discharge performance of lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of topological insulator materials technology, specifically relating to a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material and its preparation method. Background Technology

[0002] Lithium-sulfur batteries are considered strong contenders for next-generation energy storage systems due to their numerous advantages. However, lithium-sulfur batteries suffer from a shuttle effect, where certain active materials or intermediate products migrate back and forth between the positive and negative electrodes during charging and discharging. This phenomenon is particularly common in lithium-sulfur batteries, significantly negatively impacting battery performance and hindering their practical application.

[0003] To address the most serious problem in lithium-sulfur batteries—the shuttle effect—researchers have developed numerous strategies, such as sulfur cathode host material design, separator modification, and anode protection. Among these, separator modification is a relatively simple and effective strategy. Topological insulators among metal chalcogenides, as an emerging material, are considered to have broad potential for energy conversion and storage. Topological insulators are topological quantum materials that are bulk insulated but have metallic edges or surfaces. They possess a series of excellent properties, including protected surface states, narrow bulk band gaps, and high surface carrier mobility, offering potential advantages for energy conversion and storage. Some metal compounds exhibit metallicity or narrow band gaps, which can accelerate electron transfer and alleviate the insulation problem of sulfur. Simultaneously, they have strong adsorption properties for lithium polysulfides (Li₂Sn, 4≤n≤8), effectively suppressing the shuttle effect.

[0004] As a typical topological insulator, Bi₂Te₃ is considered an ideal material for modifying lithium-sulfur batteries due to its unique electronic structure (surface states are topologically protected) and two-dimensional layered structure. However, the adsorption and catalytic activity of Bi₂Te₃ for polysulfides still need further improvement. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings and deficiencies of the prior art and provide a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material. The introduction of Cu enhances the catalytic activity of Bi2Te3 for polysulfide conversion and improves ionic conductivity, thereby improving the charge and discharge performance of lithium-sulfur batteries.

[0006] This invention is achieved through the following technical solution: This invention provides a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material, with the chemical formula Bi. 2- x Cu x Te3; wherein the Cu doping amount x is less than 10%.

[0007] In the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material provided by this invention, the topological structure of the Bi2Te3 surface is changed by Cu doping, which increases the carrier concentration on the surface. At the same time, when used as a separator material for lithium-sulfur batteries, Cu doping will induce crystal defects, thereby exposing more sites. In addition, Cu and sulfur species can form Cu-S bonds, thus significantly enhancing the ability of bismuth telluride to capture polysulfides. The introduction of Cu improves the catalytic activity of Bi2Te3 for polysulfide conversion, improves ionic conductivity, and thus improves the charge and discharge performance of lithium-sulfur batteries.

[0008] Furthermore, the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material has a diameter of 200-800 nm and a thickness of 4-20 nm.

[0009] This invention also provides a method for preparing copper-doped bismuth telluride battery separator modification materials, comprising the following steps: Bismuth source and sodium tellurite were dissolved in a reaction solvent and stirred until dissolved to obtain a first reaction solution. A copper source was added to the first reaction solution to obtain a second reaction solution. The second reaction solution was reacted at 160℃-240℃ to generate a reaction product. The reaction product was cooled to room temperature, centrifuged, washed, and dried to obtain a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0010] Further, in the step of adding a copper source to the first reaction solution to obtain the second reaction solution, the mass-volume ratio of the added copper source to the reaction solvent is (0-1.1):1, in mg / mL. The mass-volume ratio of the added copper source to the reaction solvent is controlled at (0-1.1):1, in mg / mL, so that the copper doping ratio is no greater than 10%.

[0011] Further, in the step of adding a copper source to the first reaction solution to obtain the second reaction solution, the copper source includes, but is not limited to, at least one of copper nitrate, copper chloride, copper iodide, copper sulfate, or copper oxide.

[0012] Further, in the step of dissolving bismuth source and sodium tellurite in the reaction solvent and stirring until dissolved to obtain the first reaction solution, the mass-volume ratio of the amount of bismuth source added to the reaction solvent is (1-40):1, with units of mg / mL.

[0013] Further, in the step of dissolving the bismuth source and sodium tellurite in the reaction solvent and stirring until dissolved to obtain the first reaction solution, the bismuth source includes, but is not limited to, at least one of bismuth nitrate, bismuth chloride, bismuth oxide, bismuth nitrate-containing water of crystallization, bismuth chloride-containing water of crystallization, and bismuth oxide-containing water of crystallization.

[0014] Further, in the step of dissolving bismuth source and sodium tellurite in the reaction solvent and stirring until dissolved to obtain the first reaction solution, the surfactant is dissolved in the reaction solvent, a strong base is added to the reaction solvent, and then the bismuth source and sodium tellurite are added.

[0015] The present invention also provides the application of the above-mentioned bismuth telluride topological insulator lithium-sulfur battery separator material in the field of lithium-sulfur battery separators.

[0016] To better understand and implement this invention, the following detailed description is provided in conjunction with the accompanying drawings. Attached Figure Description

[0017] Figure 1 This is a flowchart illustrating the preparation method of a doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0018] Figure 2 This is the XRD pattern of a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0019] Figure 3 It's Bi 1.94 Cu 0.06 TEM images and b, d HRTEM images of Te3 and Bi2Te3.

[0020] Figure 4 It's Bi 1.94 Cu 0.06 Optical photographs of Te3 and Bi2Te3 interacting in Li2S6 solution for 24 h, and the corresponding UV-Vis spectra.

[0021] Figure 5 It's Bi 1.94 Cu 0.06 Lithium-sulfur batteries using Te3 as a separator modifier achieve a performance of 0.1 mV / s. -1 The CV curves for the first three cycles at the sweep speed.

[0022] Figure 6 Lithium-sulfur batteries using Bi2Te3 as the separator modification material achieve a performance of 0.1 mV / s. -1 The CV curves for the first three cycles at the sweep speed.

[0023] Figure 7 It's Bi 1.94 Cu 0.06 The cycling performance of lithium-sulfur batteries using Te3 and Bi2Te3 as membrane modification materials at 0.2 C.

[0024] Figure 8 It's Bi 1.94 Cu 0.06 Te3, Bi2Te3, Bi 1.98 Cu 0.02 Te3, Bi1.92 Cu 0.08 The cycling performance of lithium-sulfur batteries with Te3 as the separator modification material at 1 C.

[0025] Figure 9 It's Bi 1.94 Cu 0.06 The rate performance of lithium-sulfur batteries using Te3 and Bi2Te3 as separator modification materials at different current densities. Detailed Implementation

[0026] The embodiments of the present invention will be further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and not intended to limit the scope of the invention. Furthermore, it should be noted that, for ease of description, the accompanying drawings show only the parts relevant to the embodiments of the present invention, and not all structures.

[0027] Furthermore, the terms "first," "second," "third," etc., used in the specification and claims are only for the purpose of distinguishing the description of the same technical features and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated, nor necessarily the order of description or chronological sequence. Where appropriate, the terms are interchangeable. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature.

[0028] Similarly, the terms "fixed" and "connected" are used in the specification and claims and should not be construed as limited to a direct connection. Therefore, the expression "device A is connected to device B" should not be limited to device A being directly connected to device B in a device or system; it means that there is a path between device A and device B, which can be a path that includes other devices or tools.

[0029] Example 1 This embodiment provides a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material with the chemical formula Bi. 2- x Cu x Te3; wherein the Cu doping amount x is less than 10%.

[0030] In the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material provided in this embodiment, the topological structure of the Bi2Te3 surface is changed by Cu doping, which increases the carrier concentration on the surface. At the same time, when used as a separator material for lithium-sulfur batteries, Cu doping will induce crystal defects, thereby exposing more sites. In addition, Cu and sulfur species can form Cu-S bonds, thus significantly enhancing the ability of bismuth telluride to capture polysulfides. The introduction of Cu improves the catalytic activity of Bi2Te3 for polysulfide conversion, improves ionic conductivity, and thus improves the charge and discharge performance of lithium-sulfur batteries.

[0031] In this invention, the Cu doping amount x is less than 10% to ensure that Cu doping is beneficial to improving the charge and discharge performance of lithium-sulfur batteries. If the Cu doping amount is too large, CuTe2 phase will be generated.

[0032] In this embodiment, the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material has a diameter of 200-800 nm and a thickness of 4-20 nm.

[0033] When using bismuth telluride topological insulator lithium-sulfur battery separator materials, the diameter is controlled to be 200-800 nm and the thickness to be 4-20 nm to improve the ability to capture polysulfides. In one embodiment, the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material has a diameter of 200 nm and a thickness of 4 nm. In another embodiment, the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material has a diameter of 200 nm and a thickness of 20 nm. In yet another embodiment, the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material has a diameter of 400 nm and a thickness of 10 nm.

[0034] The copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material provided in this embodiment has a two-dimensional structure. As a separator material in lithium-sulfur batteries, it can significantly improve the electrochemical performance of lithium-sulfur batteries. The copper-doped bismuth telluride separator material has the characteristics of simple process equipment, high production efficiency, and small material consumption, making it suitable for widespread application.

[0035] Example 2 This embodiment provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1. Figure 1 This is a flowchart illustrating the preparation method of copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material. Please refer to [link / reference]. Figure 1 The preparation method of copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material includes the following steps: Step S1: Dissolve the bismuth source and sodium tellurite in the reaction solvent and stir until dissolved to obtain the first reaction solution; Step S2: Add a copper source to the first reaction solution to obtain the second reaction solution; Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product; Step S4: Cool the reaction product to room temperature, centrifuge, wash, and dry to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0036] In step S1, bismuth source and sodium tellurite are dissolved in the reaction solvent and stirred until dissolved to obtain the first reaction solution. In this process, surfactant is dissolved in the reaction solvent, a strong base is added to the reaction solvent, and then bismuth source and sodium tellurite are added.

[0037] In one embodiment, the reaction solvent includes one of water, methanol, ethanol, and ethylene glycol. The surfactant includes polyvinylpyrrolidone (PVP) with a weight-average molecular weight (Mw) of 60,000 g / mol, and the mass-to-volume ratio of PPVP to the reaction solvent is 2-100 mg / mL.

[0038] A strong base is added to provide an alkaline reaction environment. The strong base includes sodium hydroxide or potassium hydroxide. The mass-volume ratio of the added strong base to the reaction solvent is (10-30):1, with units of mg / mL.

[0039] In this embodiment, the bismuth source includes at least one of bismuth nitrate, bismuth chloride, bismuth oxide, bismuth nitrate-containing water of crystallization, bismuth chloride-containing water of crystallization, and bismuth oxide-containing water of crystallization.

[0040] The mass-to-volume ratio of bismuth source to reaction solvent is (1-40):1, in mg / mL. In step S2, copper source is added to the first reaction solution to obtain the second reaction solution, wherein the mass-to-volume ratio of copper source to reaction solvent is (0-1.1):1, in mg / mL. The mass-to-volume ratio of copper source to reaction solvent is controlled at (0-1.1):1, in mg / mL, to ensure that the copper doping ratio is no greater than 10%. If the Cu doping amount is too high, a CuTe2 phase will be formed.

[0041] In this embodiment, the copper source includes, but is not limited to, at least one of copper nitrate, copper chloride, copper iodide, copper sulfate, or copper oxide. The molar ratio of the added bismuth source, sodium tellurite, and copper source is 1 : (1.5 + 0.5x) : x; where x is the proportion of copper doping, and x is 0-10%.

[0042] In one embodiment, the copper source includes copper chloride, and the mass-volume ratio of the amount added to the reaction solvent is (0-1.1):1, in mg / mL.

[0043] Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product, wherein the reaction time is 12-48 hours to ensure the reaction is complete.

[0044] In step S4, the reaction product is cooled to room temperature, centrifuged, washed, and dried to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery membrane material. The drying temperature is 40-80℃ and the drying time is 8-20h. Methanol, ethanol, or acetone are used for centrifugation and washing.

[0045] Specifically, after the reaction product is cooled to room temperature, the product is collected by centrifugation and washed three times each with deionized water and organic solvent. Finally, it is dried in an oven at 40-80℃ for 8-20 h to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0046] Example 3 This embodiment provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1, including the following steps: Step S1: Dissolve the bismuth source and sodium tellurite in the reaction solvent and stir until dissolved to obtain the first reaction solution.

[0047] In one embodiment, a surfactant is dissolved in a reaction solvent, a strong base is added to the reaction solvent, followed by the addition of a bismuth source and sodium tellurite. The surfactant includes polyvinylpyrrolidone (PVP), the reaction solvent includes ethylene glycol, and the strong base includes NaOH. 0.5 g of PVP is added to 36 mL of ethylene glycol (EG) and stirred overnight until completely dissolved. Then, 0.4 g of NaOH is added to the reaction solvent and stirred for 30 min until completely dissolved. Finally, 0.315 g (1.0 mmol) of BiCl3 and 0.340 g (1.53 mmol) of Na2TeO3 are added, and the mixture is stirred vigorously to obtain a homogeneous first reaction solution.

[0048] Step S2: Add a copper source to the first reaction solution to obtain the second reaction solution.

[0049] In this embodiment, the copper source includes copper chloride. In one implementation, 8 mg (0.06 mmol) of CuCl2 is added to the first reaction solution, and the mixture is stirred vigorously for 1 hour to obtain the second reaction solution.

[0050] Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product.

[0051] In this embodiment, the second reaction solution was transferred to a 50 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, then the reactor was sealed and heated to 180°C for 36 h to generate the reaction product.

[0052] Step S4: Cool the reaction product to room temperature, centrifuge, wash, and dry to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0053] In this embodiment, after the reaction product was cooled to room temperature, the precipitate was collected by centrifugation and washed three times each with deionized water and ethanol, and then dried in an oven at 60 °C for 12 h. The dried precipitate was collected to obtain a high-performance copper-doped bismuth telluride topological insulator lithium-sulfur battery membrane material Bi. 1.94 Cu 0.06 Te3.

[0054] Comparative Example 1 This comparative example provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1, comprising the following steps: Add 0.5 g of polyvinylpyrrolidone (PVP) to 36 mL of ethylene glycol (EG) and stir overnight until completely dissolved. Then add 0.4 g of NaOH to the reaction solvent and stir for 30 min until completely dissolved. Add 0.315 g (1.0 mmol) of BiCl3 and 0.332 g (1.50 mmol) of Na2TeO3 and stir vigorously to obtain a homogeneous first reaction solution. The obtained first reaction solution was transferred to a 50 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, then the reactor was sealed and heated to 180°C for 36 h to generate the reaction product. After the reaction product was cooled to room temperature, the precipitate was collected by centrifugation and washed three times each with deionized water and ethanol. The precipitate was then dried in an oven at 60 °C for 12 h. The dried precipitate was collected to obtain the lithium-sulfur battery membrane material Bi2Te3.

[0055] The performance of the lithium-sulfur battery separator material Bi2Te3 prepared in this comparative example was tested.

[0056] Bi from Example 3 1.94 Cu 0.06 Te3 was used as the test sample, and Bi2Te3 of Comparative Example 1 was used as the control sample for performance characterization tests.

[0057] Bi was coated using a surface coating method 1.94 Cu 0.06 Te3 is used to prepare and form the separator for the test sample battery: 70 wt% of sample Bi 1.94 Cu 0.06Te3, 20 wt% carbon black (Super P), and 10 wt% polyvinylidene fluoride (PVDF) were thoroughly mixed in N-methylpyrrolidone (NMP) solvent to form a homogeneous slurry. This slurry was then coated onto a clean Celgard 2500 polypropylene (PP) membrane to form a functionalized membrane. The functionalized membrane was vacuum-dried overnight at 50 °C and then cut into 19 mm diameter discs, with the functionalized film serving as the interlayer material having an areal loading of approximately 0.3 mg cm⁻¹. -2 .

[0058] Bi2Te3 was used to prepare a comparative battery separator using a surface coating method: 70 wt% of sample Bi2Te3, 20 wt% of carbon black (Super P), and 10 wt% of polyvinylidene fluoride (PVDF) were thoroughly mixed in N-methylpyrrolidone (NMP) solvent to form a homogeneous slurry. This slurry was then coated onto a clean Celgard 2500 polypropylene (PP) membrane to form a functionalized membrane. The functionalized membrane was vacuum-dried overnight at 50 °C and then cut into discs with a diameter of 19 mm. The areal loading of the functionalized film as the interlayer material was approximately 0.3 mg cm⁻¹. -2 .

[0059] Figure 2 This is the XRD pattern of a copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material, in which... Figure 2 (a) shows the XRD patterns of the test sample and the control sample. Figure 2 (b) Example diagrams showing the characteristic peak shifts of the test and control samples, corresponding to crystal card ICSD#85-0439. Please refer to [link to ICSD#85-0439]. Figure 2 The copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material has a trigonal crystal structure, corresponding to the ICSD#85-0439 crystal card, with unit cell parameters a=4.368 Å, b=4.368 Å, c=30.423 Å; α=β=90°, γ=120°. The test sample is Bi... 1.92 Cu 0..08 The characteristic peak of Te3 shifts to the left compared to the control sample Bi2Te3, the diffraction angle 2θ decreases, and the interplanar spacing d increases, indicating that Cu was successfully doped into Bi2Te3.

[0060] Figure 3 It's Bi 1.94 Cu 0.06 TEM images and b, d HRTEM images of Te3 and Bi2Te3, among which Figure 3 (a) is a TEM image of Bi2Te3. Figure 3 (b) is the HRTEM image of Bi2Te3. Figure 3 (c) is Bi 1.94 Cu 0.06 TEM image of Te3 Figure 3 (d) is Bi 1.94 Cu 0.06 HRTEM plot of Te3. See also Figure 3 The test sample and the control sample were characterized by transmission electron microscopy (TEM). The test sample Bi... 1.94 Cu 0.06 Te3 exhibits a regular hexagonal plate-like morphology with a diameter of approximately 500 nm, and the lattice fringe spacing of the main peak (110) crystal plane is 0.232 nm, which is greater than that of the comparative sample Bi2Te3.

[0061] Figure 4 It's Bi 1.94 Cu 0.06 Optical photographs and corresponding UV-Vis spectra of Te3 and Bi2Te3 interacting in Li2S6 solution for 24 hours. (See also...) Figure 4 Contains test sample Bi 1.94 Cu 0.06 The UV-Vis absorption peak of Li2S6 was lowest in the Te3 solution, indicating that the tested sample Bi 1.94 Cu 0.06 Te3 has a stronger adsorption capacity for Li2S6 molecules.

[0062] Figure 5 It's Bi 1.94 Cu 0.06 Lithium-sulfur batteries using Te3 as a separator modifier achieve a performance of 0.1 mV / s. -1 The CV curves for the first three cycles at the sweep speed. Figure 6 Lithium-sulfur batteries using Bi2Te3 as the separator modification material achieve a performance of 0.1 mV / s. -1 The CV curves for the first three revolutions at the specified scan speed. Please refer to [link / reference]. Figure 5 and Figure 6 At 0.1 mVs -1 Test sample Bi 1.94 Cu 0.06 The first three cycles of Te3 showed good coincidence of cyclic voltammetry (CV), proving that Bi 1.94 Cu 0.06 Te3 exhibits excellent catalytic stability. Compared to the control sample Bi2Te3 in Comparative Example 1, the tested sample has a larger peak current, demonstrating that it has better catalytic activity for polysulfide conversion.

[0063] Figure 7 It's Bi 1.94 Cu 0.06Lithium-sulfur batteries using Te3 and Bi2Te3 as separator modification materials exhibited good cycle performance at 0.2 C. A lithium-sulfur battery assembled with a Bi2Te3-PP separator showed an initial cycle performance of 1285 mAh g⁻¹ at 0.2 C. -1 The specific capacity was 46.5% after 100 cycles.

[0064] Figure 8 It's Bi 1.94 Cu 0.06 Te3, Bi2Te3, Bi 1.98 Cu 0.02 Te3, Bi 1.92 Cu 0.08 The cycling performance of lithium-sulfur batteries using Te3 as a separator modification material at 1 C is described. Please refer to [link / reference]. Figure 7 , with Bi 1.94 Cu 0.06 The lithium-sulfur battery assembled with Te3-PP as the battery separator exhibited an initial cycle performance of 1279.6 mAh g⁻¹ at 0.2 C rate. -1 It has a high specific capacity, and after 100 cycles, the capacity retention rate is 54.6%, which is better than the 46.5% of the control sample Bi2Te3.

[0065] Figure 9 It's Bi 1.94 Cu 0.06 Rate performance of lithium-sulfur batteries using Te3 and Bi2Te3 as separator modifying materials at different current densities. (See also: [link to relevant documentation]) Figure 8 After doping modification, the test sample Bi 1.94 Cu 0.06 Te3 retains 676.6 mAh g⁻¹ after 200 cycles at 1C current density. -1 It exhibits high discharge capacity with a capacity retention rate exceeding 62.5%, which is higher than the 626.4 mAh g / L of the Bi2Te3-PP separator. -1 (53.7%). The rate performance of the battery was tested at different rates using Bi... 1.94 Cu 0.06 The capacity of the Te3-PP battery was superior to that of the Bi2Te3-PP separator at all rates, indicating that using Cu-doped Bi2Te3 as a separator for lithium-sulfur batteries can exhibit better battery performance.

[0066] Example 4 This embodiment provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1, including the following steps: Step S1: Dissolve the bismuth source and sodium tellurite in the reaction solvent and stir until dissolved to obtain the first reaction solution.

[0067] In one embodiment, a surfactant is dissolved in a reaction solvent, a strong base is added to the reaction solvent, followed by a bismuth source and sodium tellurite. The surfactant includes polyvinylpyrrolidone (PVP), the reaction solvent includes ethylene glycol, and the strong base includes NaOH. 0.5 g of PVP is added to 36 mL of ethylene glycol (EG) and stirred overnight until completely dissolved. Then, 0.4 g of NaOH is added to the reaction solvent and stirred for 30 min until completely dissolved. Finally, 0.315 g (1.0 mmol) of BiCl3 and 0.35 g (1.51 mmol) of Na2TeO3 are added, and the mixture is stirred vigorously to obtain a homogeneous first reaction solution.

[0068] Step S2: Add a copper source to the first reaction solution to obtain the second reaction solution.

[0069] In this embodiment, the copper source includes copper chloride. In one implementation, 3 mg (0.02 mmol) of CuCl2 is added to the first reaction solution, and the mixture is stirred vigorously for 1 hour to obtain the second reaction solution.

[0070] Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product.

[0071] In this embodiment, the second reaction solution was transferred to a 50 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, then the reactor was sealed and heated to 180°C for 36 h to generate the reaction product.

[0072] Step S4: Cool the reaction product to room temperature, centrifuge, wash, and dry to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0073] In this embodiment, after the reaction product was cooled to room temperature, the precipitate was collected by centrifugation and washed three times each with deionized water and ethanol, and then dried in an oven at 60 °C for 12 h. The dried precipitate was collected to obtain a high-performance copper-doped bismuth telluride topological insulator lithium-sulfur battery membrane material Bi. 1.98 Cu 0.2 Te3.

[0074] Example 5 This embodiment provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1, including the following steps: Step S1: Dissolve the bismuth source and sodium tellurite in the reaction solvent and stir until dissolved to obtain the first reaction solution.

[0075] In one embodiment, a surfactant is dissolved in a reaction solvent, a strong base is added to the reaction solvent, followed by a bismuth source and sodium tellurite. The surfactant includes polyvinylpyrrolidone (PVP), the reaction solvent includes ethylene glycol, and the strong base includes NaOH. 0.5 g of PVP is added to 36 mL of ethylene glycol (EG) and stirred overnight until completely dissolved. Then, 0.4 g of NaOH is added to the reaction solvent and stirred for 30 min until completely dissolved. Finally, 0.315 g (1.0 mmol) of BiCl3 and 0.341 g (1.54 mmol) of Na2TeO3 are added, and the mixture is stirred vigorously to obtain a homogeneous first reaction solution.

[0076] Step S2: Add a copper source to the first reaction solution to obtain the second reaction solution.

[0077] In this embodiment, the copper source includes copper chloride. In one implementation, 11 mg (0.08 mmol) of CuCl2 is added to the first reaction solution, and the mixture is stirred vigorously for 1 hour to obtain the second reaction solution.

[0078] Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product.

[0079] In this embodiment, the second reaction solution was transferred to a 50 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, then the reactor was sealed and heated to 180°C for 36 h to generate the reaction product.

[0080] Step S4: Cool the reaction product to room temperature, centrifuge, wash, and dry to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0081] In this embodiment, after the reaction product was cooled to room temperature, the precipitate was collected by centrifugation and washed three times each with deionized water and ethanol, and then dried in an oven at 60 °C for 12 h. The dried precipitate was collected to obtain a high-performance copper-doped bismuth telluride topological insulator lithium-sulfur battery membrane material Bi. 1.92 Cu 0..08 Te3.

[0082] Example 6 This embodiment provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1, including the following steps: Step S1: Dissolve the bismuth source and sodium tellurite in the reaction solvent and stir until dissolved to obtain the first reaction solution.

[0083] In one embodiment, a surfactant is dissolved in a reaction solvent, a strong base is added to the reaction solvent, followed by a bismuth source and sodium tellurite. The surfactant includes polyvinylpyrrolidone (PVP), the reaction solvent includes ethylene glycol, and the strong base includes NaOH. 0.5 g of PVP is added to 36 mL of ethylene glycol (EG) and stirred overnight until completely dissolved. Then, 0.4 g of NaOH is added to the reaction solvent and stirred for 30 min until completely dissolved. Finally, 0.315 g (1.0 mmol) of BiCl3 and 0.340 g (1.53 mmol) of Na2TeO3 are added, and the mixture is stirred vigorously to obtain a homogeneous first reaction solution.

[0084] Step S2: Add a copper source to the first reaction solution to obtain the second reaction solution.

[0085] In this embodiment, the copper source includes copper chloride. In one implementation, 8 mg (0.06 mmol) of CuCl2 is added to the first reaction solution, and the mixture is stirred vigorously for 1 hour to obtain the second reaction solution.

[0086] Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product.

[0087] In this embodiment, the second reaction solution was transferred to a 50 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, then the reactor was sealed and heated to 220°C for 36 h to generate the reaction product.

[0088] Step S4: Cool the reaction product to room temperature, centrifuge, wash, and dry to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0089] In this embodiment, after the reaction product was cooled to room temperature, the precipitate was collected by centrifugation and washed three times each with deionized water and ethanol, and then dried in an oven at 60 °C for 12 h. The dried precipitate was collected to obtain a high-performance copper-doped bismuth telluride topological insulator lithium-sulfur battery membrane material Bi. 1.94 Cu 0..06 Te3.

[0090] Example 7 This embodiment provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1, including the following steps: Step S1: Dissolve the bismuth source and sodium tellurite in the reaction solvent and stir until dissolved to obtain the first reaction solution.

[0091] In one embodiment, a surfactant is dissolved in a reaction solvent, a strong base is added to the reaction solvent, followed by a bismuth source and sodium tellurite. The surfactant includes polyvinylpyrrolidone (PVP), the reaction solvent includes ethylene glycol, and the strong base includes NaOH. 0.5 g of PVP is added to 36 mL of ethylene glycol (EG) and stirred overnight until completely dissolved. Then, 0.4 g of NaOH is added to the reaction solvent and stirred for 30 min until completely dissolved. Finally, 0.4 g (1.27 mmol) of BiCl3 and 0.340 g (1.53 mmol) of Na2TeO3 are added, and the mixture is stirred vigorously to obtain a homogeneous first reaction solution.

[0092] Step S2: Add a copper source to the first reaction solution to obtain the second reaction solution.

[0093] In this embodiment, the copper source includes copper chloride. In one implementation, 11 mg (0.06 mmol) of CuCl2 is added to the first reaction solution, and the mixture is stirred vigorously for 1 hour to obtain the second reaction solution.

[0094] Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product.

[0095] In this embodiment, the second reaction solution was transferred to a 50 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, then the reactor was sealed and heated to 240°C for 36 h to generate the reaction product.

[0096] Step S4: Cool the reaction product to room temperature, centrifuge, wash, and dry to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0097] In this embodiment, after the reaction product was cooled to room temperature, the precipitate was collected by centrifugation and washed three times each with deionized water and ethanol, and then dried in an oven at 60 °C for 12 h. The dried precipitate was collected to obtain a high-performance copper-doped bismuth telluride topological insulator lithium-sulfur battery membrane material Bi. 1.94 Cu 0.06 Te3.

[0098] Example 8 This embodiment provides a method for preparing the copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material of Example 1, including the following steps: Step S1: Dissolve the bismuth source and sodium tellurite in the reaction solvent and stir until dissolved to obtain the first reaction solution.

[0099] In one embodiment, a surfactant is dissolved in a reaction solvent, a strong base is added to the reaction solvent, followed by a bismuth source and sodium tellurite. The surfactant includes polyvinylpyrrolidone (PVP), the reaction solvent includes ethylene glycol, and the strong base includes NaOH. 0.5 g of PVP is added to 36 mL of ethylene glycol (EG) and stirred overnight until completely dissolved. Then, 0.4 g of NaOH is added to the reaction solvent and stirred for 30 min until completely dissolved. Finally, 0.01 g (0.0317 mmol) of BiCl3 and 0.340 g (1.53 mmol) of Na2TeO3 are added, and the mixture is stirred vigorously to obtain a homogeneous first reaction solution.

[0100] Step S2: Add a copper source to the first reaction solution to obtain the second reaction solution.

[0101] In this embodiment, the copper source includes copper chloride. In one implementation, 11 mg (0.06 mmol) of CuCl2 is added to the first reaction solution, and the mixture is stirred vigorously for 1 hour to obtain the second reaction solution.

[0102] Step S3: React the second reaction solution at 160℃-240℃ to generate the reaction product.

[0103] In this embodiment, the second reaction solution was transferred to a 50 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene, then the reactor was sealed and heated to 160°C for 36 h to generate the reaction product.

[0104] Step S4: Cool the reaction product to room temperature, centrifuge, wash, and dry to obtain copper-doped bismuth telluride topological insulator lithium-sulfur battery separator material.

[0105] In this embodiment, after the reaction product was cooled to room temperature, the precipitate was collected by centrifugation and washed three times each with deionized water and ethanol, and then dried in an oven at 60 °C for 12 h. The dried precipitate was collected to obtain a high-performance copper-doped bismuth telluride topological insulator lithium-sulfur battery membrane material Bi. 1.94 Cu 0.06 Te3.

[0106] This invention is not limited to the above-described embodiments. If any modifications or variations to this invention do not depart from the spirit and scope of this invention, and if such modifications and variations fall within the scope of the claims and equivalent technologies of this invention, then this invention also intends to include such modifications and variations.

Claims

1. The application of a copper-doped bismuth telluride topological insulator membrane modification material in the field of lithium-sulfur battery membranes, characterized in that, The copper-doped bismuth telluride topological insulator membrane modification material is used for the adsorption of polysulfides in lithium-sulfur batteries. The preparation method of copper-doped bismuth telluride topological insulator membrane modified material includes the following steps: The bismuth source and sodium tellurite were dissolved in the reaction solvent and stirred until dissolved to obtain the first reaction solution; A copper source is added to the first reaction solution to obtain a second reaction solution; wherein the mass-volume ratio of the amount of copper source added to the reaction solvent is (0-1.1):1, in mg / mL. The second reaction solution was reacted at 160℃-240℃. The reaction product was cooled to room temperature, centrifuged, washed, and dried to generate the reaction product. The reaction product was cooled to room temperature, centrifuged, washed, and dried to obtain a copper-doped bismuth telluride topological insulator membrane modified material with the chemical formula Bi. 1.94 Cu 0.06 Te3.

2. The application of the copper-doped bismuth telluride topological insulator membrane modification material according to claim 1 in the field of lithium-sulfur battery membranes, characterized in that: In the step of adding a copper source to the first reaction solution to obtain the second reaction solution, the copper source includes at least one of copper nitrate, copper chloride, copper iodide, copper sulfate, or copper oxide.

3. The application of the copper-doped bismuth telluride topological insulator membrane modification material according to claim 1 in the field of lithium-sulfur battery membranes, characterized in that: In the step of dissolving bismuth source and sodium tellurite in the reaction solvent and stirring until dissolved to obtain the first reaction solution, the mass-volume ratio of the amount of bismuth source added to the reaction solvent is (1-40):1, with units of mg / mL.

4. The application of the copper-doped bismuth telluride topological insulator membrane modification material according to claim 3 in the field of lithium-sulfur battery membranes, characterized in that: In the step of dissolving a bismuth source and sodium tellurite in a reaction solvent and stirring until dissolved to obtain a first reaction solution, the bismuth source includes at least one of bismuth nitrate, bismuth chloride, bismuth oxide, bismuth nitrate-containing water of crystallization, bismuth chloride-containing water of crystallization, and bismuth oxide-containing water of crystallization.

5. The application of the copper-doped bismuth telluride topological insulator membrane modification material according to claim 3 in the field of lithium-sulfur battery membranes, characterized in that: In the step of dissolving bismuth source and sodium tellurite in the reaction solvent and stirring until dissolved to obtain the first reaction solution, the surfactant is dissolved in the reaction solvent, a strong base is added to the reaction solvent, and then the bismuth source and sodium tellurite are added.

6. The application of the copper-doped bismuth telluride topological insulator membrane modification material according to claim 1 in the field of lithium-sulfur battery membranes, characterized in that: The copper-doped bismuth telluride topological insulator membrane modified material has a diameter of 200-800 nm and a thickness of 4-20 nm.

Citation Information

Patent Citations

  • Bismuth telluride nano-materials with different morphology and synthetic method thereof

    CN106145064A